2015
DOI: 10.3988/jcn.2015.11.2.142
|View full text |Cite|
|
Sign up to set email alerts
|

Feasibility of Using a Mobile Application for the Monitoring and Management of Stroke-Associated Risk Factors

Abstract: Background and PurposeRecent advances in information technology have created opportunities for advances in the management of stroke. The objective of this study was to test the feasibility of using a smartphone software application (app) for the management of vascular risk factors in patients with stroke.MethodsThis prospective clinical trial developed a smartphone app, the 'Korea University Health Monitoring System for Stroke: KUHMS2,' for use by patients with stroke. During a 6-month follow-up period, its fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 19 publications
1
54
0
5
Order By: Relevance
“…35 The fourth null study involved the use of a mobile app and monitoring device in stroke patients in South Korea. 42 Patients only used the mobile app 60 out of 180 days and secondary outcomes (BP, HbA1c, target waist circumference, smoking rate, drug adherence, exercise) did not differ between those who were and were not compliant with the mobile app. 42 The last study compared HTN self-care behaviors (medication adherence, PA, diet) and BP response between four groups: (a) self-care education over eight 1-hour sessions, (b) self-care education through four pamphlets, (c) self-care education through eight SMS, and (d) usual care.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…35 The fourth null study involved the use of a mobile app and monitoring device in stroke patients in South Korea. 42 Patients only used the mobile app 60 out of 180 days and secondary outcomes (BP, HbA1c, target waist circumference, smoking rate, drug adherence, exercise) did not differ between those who were and were not compliant with the mobile app. 42 The last study compared HTN self-care behaviors (medication adherence, PA, diet) and BP response between four groups: (a) self-care education over eight 1-hour sessions, (b) self-care education through four pamphlets, (c) self-care education through eight SMS, and (d) usual care.…”
Section: Resultsmentioning
confidence: 87%
“…Overall, 22 of the 28 studies (79%) demonstrated that using mobile phone features (text messaging, mobile apps, telemonitoring via mobile phones) was effective in improving behavioral and clinical outcomes. This review includes studies targeting a variety of CV conditions: CHD (12), 1829 chronic HF (6), 3035 HTN (5), 3640 stroke (2), 4142 acute coronary syndrome (1), 43 CVD (1), 44 and metabolic syndrome (1). 45 A dominant number of studies examined medication adherence as the clinical outcome (10 studies) while other studies examined outcomes such as PA, cardiac rehabilitation (CR) adherence, or a combination of CVD risk factors (blood pressure/BP, cholesterol, body mass index, weight).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in information technologies have allowed healthcare professionals to utilize mobile apps in clinical practice [7,8]. For example, in the non-cancer setting, mobile health apps can help with symptom detection and monitoring in patients with stroke and myocardial infarction [9,10]. Studies have also shown that mobile health apps can assist with medication management and provide reminders for doctor appointments with resulting improvement in self-care behavior, quality of life, and healthcare utilization [11].…”
Section: Scope Of the Problemmentioning
confidence: 99%
“…For instance, the Korea University Health Monitoring System for Stroke provides patients that experienced a past stroke with information regarding ongoing preventive vascular risk management [34]. Another example is mHealth, an application designed to aid stroke patients in long-term care such as providing instructions of care and medication management [35].…”
Section: Overview Of Strategies and Tools (Fig 3)mentioning
confidence: 99%